University students' attitudes towards the values of physical culture and sport as indicators of their social development - P. A. Kislyakov; T. T.T. Nguyen; M. S. Belov; O. A. Silaeva; E. A. Shmeleva (Russian State Vocational Pedagogical University, 2024)
Introduction. Physical culture and sports activities play a crucial role in the socialisation and personal development of individuals. Understanding students' attitudes towards the social values of sports is essential for creating an effective system of physical education and social development at a university. Aim. The present research aimed to examine the relationship between university students' attitudes towards various values of sports and their social responsibility, psychosocial well-being, commitment to moral norms, and social values as indicators of social development. Methodology and research methods. The study utilised various frameworks, including the psychology of sports concerning moral norms and values, the theory of physical education related to the social development of students through physical culture and sports, and social psychology focusing on indicators of social development. Psychodiagnostic methods employed included the Spirit of Sport (SOS) scale, Social Responsibility Scale, Portrait Value Questionnaire, Moral Foundations Questionnaire, and Subjective Well-Being Scale. The collected data were analysed using descriptive statistics, correlation and regression analysis, the Mann - Whitney U test, and the Friedman test. The research involved 323 university students aged 18 to 23 years. Results and scientific novelty. The research conducted has demonstrated that, in the realm of sports, students exhibit a greater commitment to the values of health, ethics, and respect for their opponents. The findings reveal that students' orientation towards the sports values of respect and education serves as a predictor of their social development, which is manifested in the cultivation of social responsibility. This social responsibility is, in turn, influenced by various social values, including care, independence, safety, conformity, and self-affirmation, as well as moral norms. Furthermore, it has been established that the psychosocial well-being of students and their social responsibility are interdependent characteristics. Practical significance. The theoretical and empirical findings of this study can be beneficial for the development of courses in psychology, sports pedagogy, and social psychology.